Cost and optimization in government An introduction to cost accounting, operations management and quality control - Khan, Aman (New York Routledge, 2017)
The careful management of costs and operations are two of the most essential elements of operating any successful organization, public or private. While the private sector is driven by profit-maximizing incentives to keep costs to a minimum, the public sector’s mission and goals are guided by a different set of objectives: to provide a wide range of essential goods and services to maintain social order, improve public health, revitalize the economy, and, most importantly, to improve the quality of life for its citizens. Although the objectives are different, it is just as important for public decision makers to make the best use of available resources by keeping the cost of operation to a minimum. This book demonstrates that with a careful emphasis on cost accounting, operations management, and quality control, all organizations and governments can increase efficiency, improve performance, and prepare to weather hard times.

This book is divided into three parts: Part I offers thorough coverage of cost fundamentals, with an emphasis on basic cost concepts, cost behavior, cost analysis, cost accounting, and cost control. Part II examines optimization in costs and operations in government including traditional or classical optimization with applications in inventory management and queuing, followed by mathematical programming and network analysis. Finally, Part III explores special topics in cost and optimization, in particular those related to games and decisions, productivity measurement, and quality control. Simple, accessible language and explanations are integrated throughout, and examples have been drawn from government so that readers can easily relate to them. Cost and Optimization in Government is required reading for practicing public managers and students of public administration in need of a clear, concise guide to maximizing public resource efficiency.
Part I Cost Basics : 1 Basic cost concepts. -- 2 Cost behavior. --3 Cost analysis. --4 Cost accounting. --5 Cost control. ---Part II Optimization in Government : 6 Classical optimization. --7 Mathematical programming. --8 Network analysis. ---Part III Special Topics in Cost and Optimization : 9 Games and decisions. --10 Productivity measurement. --11 Quality control. -- Beyond cost and optimization. -- Bibliography. -- Index.
Includes bibliographical references (pages 356-361) and index.
Keywords: Government productivity; Public administration -- Cost control; Public administration -- Cost effectiveness; Mathematical optimization